Thermophysical analisis of modification of the surface of the workpiece by laser radiation - M. N. Vereschagin; S. N. Tselueva; M. Yu. Tseluev (Литьë и металлургия)
The paper presents a thermophysical analysis of modifying the surface of a workpiece by laser radiation due to the melting of a layer of a doping substance previously deposited on the surface of the base metal.The process of heating a two-layer metallic system with a laser pulse with a normal distribution of power density over the beam section is considered. Under the action of a heat source of constant power, moving in a straight line at a constant speed, the process of heat propagation tends to the limiting quasistationary state, when the temperature field does not change with time and moves along with the source.The dependences obtained allow us to estimate the effect of the laser treatment mode on the distribution of temperature fields, establish the patterns of heat propagation and relate them to phase transformations in the metal.It has been established that the technological modes of exposure to laser radiation are limited by the value of the energy per pulse from 4 to 12 J. The choice of technological modes of exposure is determined by the combination of the scanning speed of the laser beam and the radiation power.